Anesthetic solution indication protocols for use in the endodontic clinic - Kuga, Milton Carlos [UNESP]; Almeida, Eran Nair Mesquita de [UNESP]; Bravo, Giovanna Righetti [UNESP]; Galvani, Lucas David [UNESP]; Jorge, Adirson [UNESP]; Keine, Kátia Cristina (Dental Press International, 2021)
Introduction: The indication of anesthetic solutions in routine endodontic treatments must be based on knowledge of the possible effects that these substances can trigger in systemically compromised patients. Aim: The aim of the present study was to prioritize the indication and discuss the possible secondary or adverse effects likely to occur with the use of substances of which anesthetic solutions are composed, during the routine treatment of root canals.
Keywords: Anesthesia; Dentistry; Endodontics